2008
DOI: 10.1097/nmd.0b013e3181773913
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Pilot Study to Evaluate the Efficacy of Sildenafil Citrate in Middle-Aged Men With Late-Onset Dysthymia

Abstract: Late onset dysthymic disorder (DD) in middle-aged and elderly men responds poorly to established antidepressants. Previous studies noted an improvement in mood accompanying sildenafil citrate treatment for erectile dysfunction. We sought to evaluate whether sildenafil's mood effects were independent of the effect on erectile function. A 6-week open label study was conducted with 20 male participants, aged 41-60 who were diagnosed with DD and who had normal erectile function. Participants were treated with sild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…More recent studies might suggest that PDE5i themselves have antidepressant effects and thereby may contribute to increased sexual pleasure. 36,37 At first glance, the positive response rate of 50% in our case series of 16 women who received PDE5i for FSD seems no better than chance. However, the original sildenafil study in men with erectile dysfunction 21 demonstrated a placebo response rate of only 25%.…”
Section: Discussionmentioning
confidence: 81%
“…More recent studies might suggest that PDE5i themselves have antidepressant effects and thereby may contribute to increased sexual pleasure. 36,37 At first glance, the positive response rate of 50% in our case series of 16 women who received PDE5i for FSD seems no better than chance. However, the original sildenafil study in men with erectile dysfunction 21 demonstrated a placebo response rate of only 25%.…”
Section: Discussionmentioning
confidence: 81%
“…Subsequently, in a small open-label study, Orr et al (2008) reported that sildenafil relieved depressive symptoms in men with dysthymia in the absence of ED, suggesting that sildenafil may have direct antidepressant effects. This may be because of the ability of sildenafil to cross the bloodbrain barrier to affect networks implicated in depression (Zhang et al, 2002) and an association with testosterone stimulation (Saraiva et al, 2009), which has also been linked to MDD .…”
Section: Discussionmentioning
confidence: 97%
“…However, 47.1% of the placebo were not depressed at the end of the study [ 39 ]. Orr et al [ 40 ] observed a positive effect of sildenafil on depressive symptoms independent of changes in EF. They suggested that these could be due to the effects of the drug on the autonomic nervous system or hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%